2023
DOI: 10.1128/mbio.00053-23
|View full text |Cite
|
Sign up to set email alerts
|

Stay or Go: Sulfolobales Biofilm Dispersal Is Dependent on a Bifunctional VapB Antitoxin

Abstract: Biofilms allow microbes to resist a multitude of stresses and stay proximate to vital nutrients. The mechanisms of entering and leaving a biofilm are highly regulated to ensure microbial survival, but are not yet well described in archaea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Ultimately, small segments of the genome may define microbiological characteristics that cannot be gleaned from global genomic analysis (such as carbohydrate metabolism, discussed in part here through analysis of CAZymes, but extends to other genes with high phenotypic influence, such as toxin-antitoxin biofilm regulation ( Lewis et al, 2023 )). We show here that when carbohydrate “appetite” is mapped to CAZyme inventory, the Caldicellulosiruptorales differ from the Thermoanaerobacterales in that many species of the former, but not the latter, can degrade microcrystalline cellulose.…”
Section: Discussionmentioning
confidence: 99%
“…Ultimately, small segments of the genome may define microbiological characteristics that cannot be gleaned from global genomic analysis (such as carbohydrate metabolism, discussed in part here through analysis of CAZymes, but extends to other genes with high phenotypic influence, such as toxin-antitoxin biofilm regulation ( Lewis et al, 2023 )). We show here that when carbohydrate “appetite” is mapped to CAZyme inventory, the Caldicellulosiruptorales differ from the Thermoanaerobacterales in that many species of the former, but not the latter, can degrade microcrystalline cellulose.…”
Section: Discussionmentioning
confidence: 99%
“…These observations might indicate a general downregulation response of this transcriptional regulator to confront stress. Target genes regulated by SSO1101 and homologs remain unknown, whereas it has been proposed that one of its targets could be the vapBC14 operon, which was also described to be upregulated in S. acidocaldarius biofilms [ 11 ]. The proteins VapB14 and VapC14 coded in this operon influence biofilm formation as well [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lewis et al reported that type II antitoxin VapB14 regulates biofilm dispersal in S. acidocaldarius through traditional toxin neutralization, but also by employing noncanonical transcriptional regulation [ 11 ]. S. acidocaldarius vapB14 and its homolog in thermoacidophile Metallosphaera sedula ( msed_0871 ) were both upregulated in biofilm cells, supporting the role of an antitoxin in biofilm regulation [ 11 ].…”
Section: Introductionmentioning
confidence: 99%